The antecedents, consequences and repair mechanisms of public distrust: A systematic literature review - Agni Shanti Mayangsari; Badri Munir Sukoco; Reinhard Bachmann; Juansih; Elisabeth Supriharyanti (International Journal of Management Reviews, 2026)
Abstract Public distrust has become a pressing challenge across governments, social enterprises (SEs) and businesses, shaping compliance, participation and legitimacy. Despite the well‐established research on trust, the scholarship on distrust remains fragmented and lacks systematic synthesis. This review addresses this gap by examining the antecedents, consequences and repair mechanisms of public distrust across organizational contexts. We conducted a systematic literature review of 54 peer‐reviewed articles published between 2006 and 2025, following the six‐step framework of Durach. Using the Gioia methodology, we identified first‐order categories such as misinformation, lack of transparency and unmet expectations and mapped them onto the multilevel framework of interpersonal, organizational and inter‐organizational distrust, complemented by sectoral distinctions between public sector organizations, SEs and business enterprises (BEs). The findings indicate that the antecedents of public distrust include policy failures, corruption and communication breakdowns, whereas the consequences range from reduced compliance and reputational decline to systemic instability. Across all organizational types, transparency emerges as the most frequently applied repair mechanism, yet its effectiveness often depends on combining it with relational, cultural and structural approaches that address underlying expectations about organizational accountability and integrity. This review advances conceptual clarity on trust and distrust by consolidating public distrust as a distinct evaluative construct, developing a multilevel, cross‐sectoral framework and clarifying how organizational responses address distrust following institutional failures. It further delineates the conditions under which trust and distrust should be analytically distinguished, particularly when stakeholders evaluate different organizational attributes. The study also identifies gaps in the literature, including the under‐representation of SEs and BEs, and calls for more diverse methodological approaches to deepen understanding of distrust and its repair.